Luruskan Punggungmu Luruskan Masa Depanmu Cegah Skoliosis Sejak Dini di SMA Negeri 3 Cimahi - Muhammad Deri Ramadhan; Sri Ulina; Vina Helviana; Silvia Agustina; Nadzira Alfi Wahyuni; Lintang Zahra Febrianti; Tiara Juliani; Dwi Lastin Nafisah; Agnes Marthen; Syndi Sofia Ristiana (Jurnal Medika: Medika, 2026)
This community health education activity was carried out to increase students’ knowledge and awareness regarding early detection and prevention of scoliosis, a spinal deformity commonly found in adolescents. The program targeted 34 students of SMA Negeri 3 Cimahi and aimed to provide accurate information about signs, risk factors, and preventive behaviors related to scoliosis. The method included preliminary assessment, coordination with school partners, health education through lectures, discussions, demonstrations of Adam’s Forward Bend Test, and distribution of educational leaflets. Evaluation was conducted through pre-test and post-test. The results showed a significant improvement, with 95% of students demonstrating better understanding of scoliosis symptoms and 90% being able to identify early detection steps. Students also displayed increased awareness of maintaining proper posture and reducing daily risk factors such as carrying heavy bags on one side. Overall, this activity effectively enhanced students’ knowledge and encouraged positive preventive behavior, supporting early scoliosis detection efforts in the school environment.